Demographics and Awareness of Diabetic Retinopathy among Diabetic Patients Attending Department of Ophthalmology at Dhulikhel Hospital - Shrestha, R. M.; Shrestha, N.; Shrestha, P.; Shrestha, J. K. (Kathmandu University Medical Journal, 2022)
Background Diabetes mellitus is considered as a major public health concern globally. Poor management of diabetes may lead to several serious complications including endstage renal disease, diabetic retinopathy, diabetic neuropathy, and cardiovascular complications. Among them diabetic retinopathy is one of the leading causes of visual impairment and blindness in Nepal. Objective To assess the demographics and level of awareness among individuals with diabetes about diabetic retinopathy during their visit to Department of Ophthalmology at Dhulikhel Hospital. Method A descriptive cross-sectional study was conducted involving all consecutive cases of diabetes mellitus who attended eye clinic with the principal investigator and co-investigator from March 2021 to August 2021. Detailed demographics of the participants, their level of awareness regarding diabetic retinopathy and associated complications were documented. This was followed by a detailed ocular examination intending to screen for the presence of features of diabetic retinopathy. Result A total of 260 patients with a mean age of 54 years ± 12.20 (range of 24 - 85 years) were included. The male to female ratio was 2.2:1. Among them, 65.4% of the patients had diabetes mellitus for less than 5 years duration. Diabetic retinopathy was found in 18.46% of the cases. Awareness of diabetic ocular complications was significantly higher among literate population (p = 0.054), among those who have positive family history of diabetes mellitus (p = 0.529) and those who had undergone prior fundus evaluation (p = 0.000). Conclusion From result of this study, we can emphasize that there is a necessity for health education in order to increase the awareness and knowledge about diabetic retinopathy to lower the burden of sight threatening complications related with the issue.